Clinical and immunological evaluation of cat‐allergic asthmatics living with or without a cat. Issue 12 (8th October 2021) - Wambre, Erik R.; Farrington, Mary; Bajzik, Veronique; DeBerg, Hannah A.; Ruddy, Marcella; DeVeaux, Michelle; Meier, Pretty; Robinson, David; Cantor, Matt; Huang, Chengrui; Orengo, Jamie M.; Wang, Claire Q.; et al.
Abstract: Background: Characterising the clinical and immunological impact of daily cat exposure in cat‐allergic subjects with asthma who live with cats (WC) and those who do not (WoC) may provide understanding of the drivers of the allergic response. Methods: Clinical and immunological characteristics (skin prick test, spirometry, symptom assessments, immunological markers) were compared between asthmatic subjects WC ( n  = 10) and WoC ( n  = 9). Results: WC subjects had greater use of long‐acting beta agonists ( p  < .05) and high‐potency corticosteroids. No differences were observed in lung function, nasal and ocular symptoms, or asthma control between the groups. Cat dander‐ and Fel d 1‐specific IgG4 concentrations were higher in WC than WoC subjects (both p  < .05). Total IgE and cat dander‐, Fel d 1‐ and Fel d 7‐specific IgE concentrations were similar, but Fel d 4‐sIgE was higher in WC subjects ( p  < .05) versus WoC. Basophil sensitivity to cat dander extract and Fel d 1 was lower in WC versus WoC subjects ( p  < .05) and correlated with higher IgG4 concentrations ( r  = 0.63; p  = .009). Fel d 1‐specific CD4+ T‐cell responses polarised toward Th2A responses in WC versus WoC subjects; Fel d 1‐specific IgE correlated with surface expression of CRTH2 and CD200R (both p  ≤ .05). Conclusion: Immunological differences observed in WC versus WoC did not reflect clinical tolerance with natural cat exposure. The ability to live with a cat despite allergy could be driven by higher preventative medication use. This study may support design of novel therapeutics for allergy management. Abstract : Exploratory study characterizing the impact of daily cat exposure in cat‐allergic subjects living with/without cats (WC/WoC). Cat dander‐ and Fel d 1‐specific IgG4 concentrations were higher in WC versus WoC subjects ( p  < .05); lower basophil sensitivity to cat dander extract/Fel d 1 in WC versus WoC subjects ( p  < .05) correlated with higher IgG4 concentrations ( r  = 0.63; p  = .009). Immunological differences not reflected in clinical tolerance with cat exposure. Fel d 1, major cat allergen; Ig, immunoglobulin; WC, with cat; WoC, without cat.